2013
DOI: 10.1186/1742-4690-10-91
|View full text |Cite
|
Sign up to set email alerts
|

The combination of arsenic, interferon-alpha, and zidovudine restores an “immunocompetent-like” cytokine expression profile in patients with adult T-cell leukemia lymphoma

Abstract: BackgroundHTLV-I associated adult T-cell leukemia/lymphoma (ATL) carries a dismal prognosis due to chemo-resistance and immuno-compromised micro-environment. The combination of zidovudine and interferon-alpha (IFN) significantly improved survival in ATL. Promising results were reported by adding arsenic trioxide to zidovudine and IFN.ResultsHere we assessed Th1/Th2/Treg cytokine gene expression profiles in 16 ATL patients before and 30 days after treatment with arsenic/IFN/zidovudine, in comparison with HTLV-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
50
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 53 publications
8
50
0
Order By: Relevance
“…Therefore, 20 years of investigation to find an effective treatment for HAM/TSP and ATL led us to test a combination therapy of peg-IFN as an immunomodulator, sodium valproate as a deacetylase inhibitor, and prednisolone as an anti-inflammatory agent in patients with HAM/TSP [10,20,25,43]. In the present study, significant improvements were observed in clinical aspects such as motor disability, spasticity, and antibody titer of HTLV-1 virus after 6 months of triple therapy; however, urinary findings and sensory disturbances with lower back pain improved marginally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, 20 years of investigation to find an effective treatment for HAM/TSP and ATL led us to test a combination therapy of peg-IFN as an immunomodulator, sodium valproate as a deacetylase inhibitor, and prednisolone as an anti-inflammatory agent in patients with HAM/TSP [10,20,25,43]. In the present study, significant improvements were observed in clinical aspects such as motor disability, spasticity, and antibody titer of HTLV-1 virus after 6 months of triple therapy; however, urinary findings and sensory disturbances with lower back pain improved marginally.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, antiviral drugs combined with the immunomodulators may be more effective for the treatment of patients with HAM/TSP. Our recent study [20] demonstrated that triple therapy with arsenic, IFN-α, and zidovudine shifts the cytokine expression from a regulatory T cell and T helper 2 phenotype to a T helper 1 phenotype. This shift enhances the eradication of ATL cells and prevents the emergence of opportunistic infections.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…valproic acid or arsenic trioxide) (Kchour et al, 2013;Olindo et al, 2011); -collaborating with industrial partners to investigate the off-label use of newly developed agents used in HTLV-1-negative T-cell lymphoma (e.g. anti-CCR4 and anti-CD30).…”
Section: Screen For Existing and Novel Drugs To Improve Therapymentioning
confidence: 99%